2019
DOI: 10.1177/2053951719855091
|View full text |Cite
|
Sign up to set email alerts
|

Digital identity: Contemporary challenges for data protection, privacy and non-discrimination rights

Abstract: The World Bank estimates that over one billion people currently lack official identity documents. To tackle this crucial issue, the United Nations included the aim to provide legal identity for all by 2030 among the Sustainable Development Goals. Technology can be a powerful tool to reach this target. In the digital age, new technologies increasingly mediate identity verification and identification of individuals. Currently, State-led and public-private initiatives use technology to provide official identifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 14 publications
1
25
0
3
Order By: Relevance
“…This was obvious through the relatively low, yet acceptable R-squared measures. Nonetheless, the study confirms what previous literature suggested regarding the relationship between identity concerns and citizens' acceptance of governmental use of personal data (Beduschi, 2019), as well as between (Ebelogu et al, 2019).…”
Section: Contribution To Theorysupporting
confidence: 90%
See 2 more Smart Citations
“…This was obvious through the relatively low, yet acceptable R-squared measures. Nonetheless, the study confirms what previous literature suggested regarding the relationship between identity concerns and citizens' acceptance of governmental use of personal data (Beduschi, 2019), as well as between (Ebelogu et al, 2019).…”
Section: Contribution To Theorysupporting
confidence: 90%
“…This study addresses the calls in previous literature to better understand concerns that citizens have about the rise of digital surveillance amidst socio-technical changes (see for example, Bernal, 2016;Cayford & Pieters, 2018;Beduschi, 2019;Ram & Gray, 2020).…”
Section: George Orwell 1984mentioning
confidence: 96%
See 1 more Smart Citation
“…Digital identity technologies are not inherently neutral. Depending on how digital identity systems are designed and used, they may lead to inequalities or discrimination and even hinder the rights of those that they intend to benefit (Beduschi, 2019).…”
Section: Digital Identity Should Not Exacerbate Pre-existing Inequalimentioning
confidence: 99%
“…Azonban az utasítás hatályba lépését megelőzően már bevett gyakorlattá vált, hogy nyilvánosan, következmények nélkül lehet a szervezetbe vetett bizalmat aláásni, hiszen nem létezett még erre vonatkozóan hivatalos állásfoglalás. A jogszabályi háttér kiegészítése az egyéb szervezetszabályzó jogi eszközzel elengedhetetlenül szükséges volt, hiszen egyáltalán nem mindegy, hogy milyen információk látnak napvilágot az online térben magánszemélyekről, szervezetekről, és azok milyen hatással vannak a digitális identitásra (Beduschi, 2019). A Google felmérése (URL1) szerint már 2001-ben is az emberek 22%-a keresett rá a saját szervezetére, amelyet a szakirodalomban ego-szörfözésnek vagy hiúsági keresésnek neveznek (Yonetani, Kitani & Sato, 2018).…”
Section: Elméleti Háttér éS Előzményekunclassified